Τhe first report of Linguatula serrata in grey wolf (Canis lupus) from Central Balkans - PAVLOVIĆ, I; PENEZIĆ, A; ĆOSIĆ, N; BURAZEROVIĆ, J; MALETIĆ, V; ĆIROVIĆ, D (Journal of the Hellenic Veterinary Medical Society, 2018)
Linguatula serrata is a cosmopolitan, bloodsucking parasite found in both domestic and wild animals. Humans are not considered as its main hosts but can act as both intermediate (visceral linguatuliasis) and final hosts (nasopharyngeal linguatuliasis). Reports on wild canids as definitive hosts of this parasite are scarce. During 2009-2011 the autopsy was performed on 42 legally hunted grey wolves (Canis lupus) from Serbia and Former Yugoslav Republic of Macedonia (FYROM). Only one specimen was infected with a single adult female of L. serrata. The parasite was found in the nasal cavity of the grey wolf. The infected male wolf was shot in the eastern part of the territory of Former Yugoslav Republic of Macedonia (FYROM). This finding is the first record of linguatuliasis in wolves from FYROM. Previous records of this parasite from the central Balkans region originated from dogs, cattle and hares. Only few records of this parasite are known for the grey wolf in general.